Contestation Of Islamic Discourse In The Digital Space On Islamic Portals - Achmad Tohari; Aviv Nafiuddin; Fathul Qorib (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
This research aims to analyze the content of Islamic media portals regarding the issue of faith in the online media Muslim.or.id and Nu.or.id. The author analyzes how Islamic media framing looks at the issue of faith, which is often discussed in everyday life, on the media portals Muslim.or.id and Nu.or.id. The author also analyzes the development of Islamic media in Indonesia by referring to the history of Islamic media in Indonesia. This research is a qualitative study in which the author uses Robert Entman's framing analysis method to analyze Muslim.or.id and Nu.or.id media portals from an Islamic perspective in their media articles. This study concludes that Islamic media portals have experienced significant development, especially the emergence of new media related to the organizations they support with their media base on the Internet after the new order, framing analysis obtained the conclusion that between Muslim.or.id and Nu.or.id in the discussion of Islam, it can be seen that both contribute to each other, but judging from the content of the posts that Muslim.or.id more often contains updates in its media content compared to Nu.or.id media, which looks more waiting for the movement of conservative media religious narrative discourse.